Main trends in minimum winter average monthly runoff change of rivers in the basin of Lake Sevan - Margarian Varduhi; Gaidukova Ekaterina; Mirzoev Vagif; Deviatov Vladimir; Victorova Natalia (E3S Web of Conferences)
The work is devoted to the assessment of the winter minimum average monthly runoff of the Lake Sevan basin. Analysis of the temporal distribution of the studied hydrological characteristics was carried out. The study used data on daily water consumption at 12 hydrological posts, located within the basin of Lake Sevan. The purpose of the research is to calculate the norm of winter minimum average monthly discharges, coefficients of variability (Cv) and skewness (Cs), minimum discharges of different security, to analyze and evaluate the patterns of modern changes in winter minimum average monthly discharges of the rivers of the Lake Sevan basin in a series of long-term observations. Reliability curves have been constructed, and the values of the minimum monthly runoff with a different security have been estimated. It has been established that the basin of Lake Sevan is distinguished by the variety of risks of minimal water flow in the winter period. The obtained statistical materials will serve as a basis for scientific generalizations of the results achieved, and can also be used for practical purposes in hydraulic engineering design, assessment of natural hazards and the adoption of appropriate preventive measures and solutions.